Developing teaching professionalism through nearpod.com integration: TPACK framework - Efendi, Tri Achmad; Silwana, Amalia; Subaidah; Nurhidayah, Sri; Putri, Nur Aini Saura; Prihantini, Apsari Fajar; Soenarmi, Fransisca R.; Sulistiyani; Widayanti, Evi; Indah, Dewi Rosaria; Julianingsih, Denok; Sari, Dian Purnama (University of Islam Malang, 2025)
This act of community service in the form of a workshop for senior high school teachers was to enhance the participants’ professionalism in teaching in the 21st century. The integration of technology is unavoidable. Therefore, this workshop is aimed at introducing one of the Learning Management Systems (LMS) named Nearpod that can help teachers teach effectively. The method used in this community service activity is Service Learning (SL) which consists of planning and preparation stage, implementation stage, and evaluation stage. In the planning and preparation stage, there are problem identification activities, distributing questionnaires about teacher’s teaching habits and pretest. The implementation stage consists of material delivery session, demonstration, practice, discussion, and assignments. Then, the evaluation stage through committee discussions that consider the results of the pretest and posttest as well as the satisfaction questionnaire that has been distributed to participants. 96 workshop participants, who are senior high school teachers in various regions of East Java Province, gave a positive response to the implementation of this workshop. There was an increase in the percentage score for the pretest (57,6%) and posttest (85,4%), which shows that there was an increase in teacher understanding and skills after attending the workshop, namely 27,8%. To conclude, this workshop activity is considered very useful for teachers in improving the quality of learning and developing teaching professionalism, especially in designing teaching and learning activities for Gen Z.